(untitled) (Bangladesh Medical Journal, 2012)
Trochanteric fractures occur in elderly osteoporotic patients with concomitant medical disorders, who are unable to tolerate lengthy periods of anaesthesia or any appreciable blood loss. For this reason, external fixation represents an attractive alternative. External fixation can be easily applied by modern equipments like c-arm. It is simple, quick, low cost with minimal surgical trauma, lower rate of morbidity, less operation time, shorter duration of hospital stay and early mobilization.This clinical study is the result of trochanteric fractures of the femur in high risk elderly patients treated with an external fixator on 11 patients over a period of 2 years from July 2005 to June 2007 at NITOR.The object of the study was to evaluate the outcome of operation. All the patients were in a poor general condition and with severe associated medical diseases and also more than one condition were present. The external fixator was removed after adequate clinical radiological sign of fracture union (averaged 16.54 weeks) as an out patient procedure. The overall radiological improvement was observed in 11 cases in 6 months followup. The overall satisfactory result was observed in 9 (81.8%) and unsatisflictory in 2(18.2%). DOI: http://dx.doi.org/10.3329/bmj.v39i3.9951 BMJ 2010; 39(3)